Insights From the Most Updated Research Regarding the Importance of Religion Impact in The Business Ethics Field: A Literature Review - Alina Beattrice VLADU; Diana Elisabeta MATICA; Dan Dacian CUZDRIOREAN (Communications of International Proceedings, 2022)
Throughout history, religious beliefs have influenced humankind and societies. As research on ethical behavior and moral reasoning continues to grow in the Business ethics field, a complementary spring of research concerning spirituality has emerged. To advance research an understanding of what has been accomplished so far is mandatory. In this regard, we conducted a review of the scientific papers published at the intersection of religion and the business ethics field in the last three years (2020-2022 period) indexed in Clarivate Analytics’ Web of Science. Having the goal to offer the most updated research on the topic, our paper summarizes the main findings and offers suggestions for future research. Based on the papers analyzed, we draw a two-fold conclusion: (1) religion continues to provide a prominent meaning system in society, being an important source of understanding both business practices and ethical behavior of individuals and organizations; (2) its impact continues to be examined on a large scale covering multiple areas beginning with family firm values and long-term goal orientation, sustainable consumption practices, interfirm trust, the charitable donation from firms with religion-declared CEO, job satisfaction and organizational commitment, social gambling to corporate social responsibility, climate change or cross-regional resource flows. Under-researched and underexplored streams of research were identified referring to the influence of religion in terms of access to leadership positions by women, the influence of religious beliefs on women entrepreneurs and women`s employment, patriarchal domination over religion deterring women’s rights and employee spiritual well-being inside organizations.
Keywords: religion; business ethics; ethical behavior; family firms